Russ and the firehouse - Rickert, Janet Elizabeth; McGahan, Pete (Bethesda, Md. : Woodbine House, 2000)
Russ, a five-year-old with Down syndrome, visits his uncle's firehouse and gets to help with the daily chores.
"A Day with Russ"--Cover.
"Down Syndrome/Special Needs--P. [4] of cover.
Keywords: Fire stations -- Juvenile literature; Fire departments -- Juvenile literature; Down syndrome -- Juvenile literature; People with mental disabilities -- Juvenile literature